Part of the Conversation: Women’s Studies in Higher Education - Alvarez, Margaret Helen U. (Silliman Journal, 2022)
The United Nations, through its millennium development goals, accords the greatest importance to the role of women graduates who, because of their training, constitute part of a country’s skilled human resources and are therefore in a position to make a significant contribution to the process of sustainable human development. Education is thus a principal means to empower women so that they realize their potential. This paper begins with an examination of the goals of higher education and the question of which of the two—equality or equity of education—must be emphasized. While there are those who suggest that equality of education should be provided, meaning identical educational opportunities for all learners, there are others who are promoting equity of education, meaning the provision of varied educational opportunities in order to achieve specified goals. Four theoretical models for considering the role and place of women in education are the conceptual approaches of pluralism, assimilation, deficit, and social justice. It is suggested that increased use of complementary characteristics may lead to a merging of the concepts of pluralism and assimilation, bringing about a system that serves all. A case is made for the inclusion and increased recognition of Women’s Studies in higher education. Many women’s studies programs have gained a degree of stability and familiarity on campuses, but the debate remains regarding its place in higher education—that is, whether to mainstream women’s studies in the traditional curriculum or to maintain it as an independent interdisciplinary field. In this paper, the growth of women’s studies programs is traced. Models from existing women’s studies programs in Philippine universities and at Macquarie University, Sydney and ICU, Tokyo are presented. It is crucial to establish an institutionalized women’s studies curriculum in higher education that provides a multidisciplinary organizational framework for individual scholars.